Short communication: A new record of Etlingera megalocheilos (Griff.) A.D. Poulsen (Zingiberaceae) in Sulawesi, Indonesia - TRIMANTO TRIMANTO; LIA HAPSARI (Society for Indonesian Biodiversity, 2018)
Trimanto, Hapsari L. 2018. Short communication: A new record of Etlingera megalocheilos (Griff.) A.D. Poulsen (Zingiberaceae) in Sulawesi, Indonesia. Biodiversitas 19: 1227-1235. A through morphological examination has been conducted to a living specimen of Zingiberaceae collection of Purwodadi Botanic Garden, East Java which was collected from Pangi Binangga Nature Reserve, Central Sulawesi. The result showed that the characters of the species match very well with the description of Etlingera megalocheilos. The distribution of E. megalocheilos was previously reported to occur only in Sundaland includes Peninsular Malaysia, Singapore, Sumatra, Java, and Borneo. Thus, E. megalocheilos is a newly recorded species in Sulawesi; and confirmed that its distribution record now has expanded to Wallacea. The key morphological characters of E. megalocheilos are labellum hourglass-shaped, dull red or red to orange-red with the yellow margin, the anther is not covered by the corolla lobe, and have slightly angled filament. Detailed descriptions, photographs, and notes of the species are presented in this paper. Due to its high potential medicinal properties, further bioprospecting studies are necessary to conduct.